2016
DOI: 10.1016/j.ajo.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patient Age on Intraocular Lens Power Prediction Error

Abstract: PE was less myopic by approximately 0.06 D per decade as age increased, suggesting that patient age should be considered when selecting IOL power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…Though the follow-up time was less than 6 months and glaucoma drainage device surgery was included in the combined group, it remains a meaningful result. Old age has been associated with structural changes of scleral collagen ber and changes of ACD [40,41], therefore, some studies reported that age of patients may affect the refractive outcomes after cataract surgery [42,43]. Our study also supports this result, as old age appeared to be risk factor up to 12 months after phacotrabeculectomy.…”
Section: Discussionsupporting
confidence: 87%
“…Though the follow-up time was less than 6 months and glaucoma drainage device surgery was included in the combined group, it remains a meaningful result. Old age has been associated with structural changes of scleral collagen ber and changes of ACD [40,41], therefore, some studies reported that age of patients may affect the refractive outcomes after cataract surgery [42,43]. Our study also supports this result, as old age appeared to be risk factor up to 12 months after phacotrabeculectomy.…”
Section: Discussionsupporting
confidence: 87%
“…The availability of larger dataset will allow to use powerful tools to systematically retrieve the best set of features 33 (i.e. those most informative, such us, lens geometrical parameters, age 34 , preoperative refraction, …) as well as a mathematical expression (N-dimensional, linear or non-linear) depending on these features to estimate the ELP.…”
Section: Discussionmentioning
confidence: 99%
“…The older age of patients in group P might be the reason for the inaccurate refractive outcome in group P. The mean age was significantly higher in the order of group P, group D, and group S, and the older age might have resulted in poor cooperation during biometry measurement and poor refractive outcome. Previous studies have shown that older age is associated with IOL power prediction error and that it can be a risk factor for higher refractive error after cataract surgery 20,21 . Besides age, there was no significant difference in AL and K between groups.…”
Section: Discussionmentioning
confidence: 99%